Application of Soil Analysis-Based Fertilization Technology to Improve Farmers’ Productivity and Income: A Quantitative Approach in Tongowai Village, Tidore, North Maluku - Anita Ninasari; Kuad Suwarno; Suleyman Suleyman; Tuti Handayani Arifin; M. Darmawan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The agricultural sector is strategic for food security and regional economic development, yet productivity in many Indonesian regions is hindered by fertilization practices that do not reflect actual soil fertility. Many farmers still apply conventional, experience-based fertilization without considering crop nutrient requirements or local soil characteristics, leading to inefficient fertilizer use and reduced land productivity. This community service program aimed to improve farmers’ knowledge and capacity to implement soil analysis–based fertilization technology to increase crop productivity and farm income. The program was implemented in Tongowai Village, Tidore, North Maluku, through extension activities, technical training, field demonstrations, follow-up assistance, and introduction of soil fertility analysis as the basis for precise fertilizer recommendations. Pre–post intervention evaluation showed quantitative improvements: average farmer knowledge scores rose from 48.2 to 79.5 (an increase of 65%); average chemical fertilizer use per hectare decreased from 420 kg to 330 kg (a 21.4% reduction); and maize yield on demonstration plots increased from 3.2 t/ha to 4.1 t/ha (a 28.1% increase). Fertilizer-use efficiency (yield per kg of fertilizer) improved from 7.6 kg/kg to 12.4 kg/kg. Short-term economic impact was observed as a mean farmer income increase of 18% for participating groups in one cropping season. These results indicate that soil analysis–based fertilization can enhance farmer knowledge, reduce inefficient fertilizer inputs, and improve productivity and income in the short term. Long-term environmental and socioeconomic impacts require continued monitoring and larger-scale effectiveness studies